Performance analysis of negative group delay network using MIMO technique - Yaqeen S. Mezaal; Marwah Al-Ogaidi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This study introduces comparative consequences that determine the bit error rate enhancements, resultant from adopting a proposed MIMO wireless model in this study. The antenna configurations for this model uses new small microstrip slotted patch antenna with multiple frequency bands at strategic operating frequencies of 2.4, 4.4, and 5.55 respectively. The S11 response of the proposed antenna for IEEE802.11 MIMO wireless network has been highly appropriate to be adopted with MIMO antenna system. The negative group delay (NGD) response is the most significant feature for projected MIMO antenna. The NGD stands for a counterintuitive singularity that interacts time advancement with wave propagation. These improvements are employed for increasing a reliability of instantly conveyed data streams, enhance the capacity of the wireless configuration and decrease the bit error rate (BER) of adopted wireless system. In addition to antenna scattering response, the enhancements have been analysed in term of BER for different MIMO topologies.